2003
DOI: 10.2170/jjphysiol.53.401
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of L(+)-Lactate and pH on Contractile Performance in Rabbit Glycerinated Skeletal Muscle

Abstract: Prolonged activation of intact skeletal muscle leads to fatigue that is characterized simply by the decrease in peak isometric tension and the maximum shortening velocity (V m ), but the mechanism of fatigue within a muscle fiber has been thought to be complex. The decline in tension generation noted during in vivo fatigue is due to the changes in various factors within a muscle cell, e.g., inadequate activation in excitationcontraction system [1,2], alterations in the calcium sensitivity of the contractile ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…While reduced pH boosts the aggregation of many sHSP substrates, it also increases the sHSP-mediated protection from aggregation [ 3 , 6 ]. Interestingly, acidosis raises the passive stiffness of skeletal muscles [ 44 ]. Although intracellular pH and oxidative stress were not measured in our biopsy samples, it is reasonable to speculate that exercise increases these parameters more in myopathic than in healthy muscles, which may then cause higher chaperone activity (possibly towards elastic titin) in the diseased cells.…”
Section: Discussionmentioning
confidence: 99%
“…While reduced pH boosts the aggregation of many sHSP substrates, it also increases the sHSP-mediated protection from aggregation [ 3 , 6 ]. Interestingly, acidosis raises the passive stiffness of skeletal muscles [ 44 ]. Although intracellular pH and oxidative stress were not measured in our biopsy samples, it is reasonable to speculate that exercise increases these parameters more in myopathic than in healthy muscles, which may then cause higher chaperone activity (possibly towards elastic titin) in the diseased cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bars, 5 µm. and myocardium (Orchard and Kentish, 1990) and can also increase passive tension (Berger et al, 1999;Miyake et al, 2003). In principle, active contraction may be enhanced by sHSP protective effects on actin, troponin, or myosin.…”
Section: Discussionmentioning
confidence: 99%
“…Contractility of myocytes is strongly affected by intracellular acidosis (Orchard and Kentish, 1990). Studies also suggested that acidosis increases the passive stiffness of the heart (Berger et al, 1999) and of skeletal muscles (Miyake et al, 2003). Intracellular acidosis induced by ischemic stress caused severe diastolic dysfunction in a double-knockout mouse model deficient for B-crystallin and HSPB2 (Golenhofen et al, 2006;Pinz et al, 2008).…”
Section: Titin Spring Elements Act As Monomers In Vitromentioning
confidence: 99%
“…and myocardium (Orchard and Kentish, 1990) and can also increase passive tension (Berger et al, 1999;Miyake et al, 2003). In principle, active contraction may be enhanced by sHSP protective effects on actin, troponin, or myosin.…”
Section: Discussionmentioning
confidence: 99%
“…Contractility of myocytes is strongly affected by intracellular acidosis (Orchard and Kentish, 1990). Studies also suggested that acidosis increases the passive stiffness of the heart (Berger et al, 1999) and of skeletal muscles (Miyake et al, 2003). Intracellular acidosis induced by ischemic stress caused severe diastolic dysfunction in a double-knockout mouse model deficient for B-crystallin and HSPB2 (Golenhofen et al, 2006;Pinz et al, 2008).…”
Section: Titin Spring Elements Act As Monomers In Vitromentioning
confidence: 99%